Generation and management of ideas: the ideando project as a local strategy for innovation (Revista Brasileira de Contabilidade e Gestão, 2018)
The article is based on the presentation of the IDEANDO project, approved by the University of the Region of Joinville - Univille - for execution in the biennium 2018- 2019. The proposal is based on the strategy of interaction between teaching and research and extension of the Univille and is constituted in systematized activities directed to the generation of innovative ideas. In addition, the project aims to raise the scene of the institutions that shape the local ecosystem of innovation and promote the integration of these actors in the cycle of ideas management until the implementation phase, at which time innovation can be opportunistic. The main desired results are a work methodology for generating and managing ideas that can be shared; an online platform of technological and social demands and a mapping of the institutions that form the innovation ecosystem of the region that surrounds the municipalities of São Bento do Sul, Rio Negrinho and Campo Alegre.
Keywords: innovation; idea management; creativity